The impact of the addition of iodoform on the physicochemical properties of an epoxy-based endodontic sealer - Kuga, Milton Carlos [UNESP]; Faria, Gisele [UNESP]; So, Marcus Vinicius; Keine, Katia Cristina [UNESP]; Santos, Alailson Domingos dos; Hungaro Duarte, Marco Antonio; Poli Kopper, Patricia Maria (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2014)
Due to the low radiopacity of Sealer 26, iodoform is frequently empirically added to this sealer. Thus, the interference of this procedure with the physicochemical properties of Sealer 26 must be evaluated. Objective: This study evaluated the influence of the addition of iodoform on setting time, flow, solubility, pH, and calcium release of an epoxy-based sealer. Material and Methods: The control group was pure Sealer 26, and the experimental groups were Sealer 26 added with 1.1 g, 0.55 g or 0.275 g of iodoform. Setting time evaluation was performed in accordance with the ASTM C266-03 speciflcation. The analysis of flow and solubility was in accordance with the ISO 6876-2001 speciflcation. For the evaluation of pH and calcium ion release, polyethylene tubes were filled with the materials and immersed in flasks with 10 ml of deionized water. After 24 h, 7, 14, 21, 28, and 45 days pH was measured. In 45 days, the calcium released was evaluated with an atomic absorption spectrophotometer. Results: The addition of iodoform increased setting time in comparison with pure sealer (P < 0.05). As for flow, solubility, and calcium release, the mixtures presented results similar to pure sealer (p > 0.05). In the 24 h period, the mixture with 1.1 g and 0.55 g of iodoform showed lower pH than pure sealer and than sealer added with 0.275 g of iodoform (P < 0.05). Conclusions: The iodoform added to Sealer 26 interferes with its setting time and solubility properties. Further studies are needed to address the clinical signiflcance of this interference.
Keywords: Endodontics; Root canal filling materials; Physical and chemical properties